Tracing Phantasms: Envisioning the Haunted Novel in Roberto Bolaño’s 2666 and Gerald Murnane’s The Plains - Stockton, Lana Jane (Curtin University, 2019)
The thesis proposes a theory of the haunted novel as a way of identifying a kind of literature that expresses relation to silent (or silenced) cultural memories through distinctive use of visual devices, which the thesis refers to as ‘phantasms’. Through the tracing of phantasms represented in the novels 2666 by Roberto Bolaño and The Plains by Gerald Murnane, the thesis imagines the haunted novel as a literary expression of unsettled history.